Processing/formulation parameters determining dispersity of chitosan particles: an ANNs study. (February 2014) - Esmaeilzadeh-Gharehdaghi, Elina; Faramarzi, Mohammad Ali; Amini, Mohammad Ali; Moazeni, Esmaeil; Amani, Amir
Abstract Although a great number of studies may be found in literature about the parameters affecting the size of chitosan nanoparticles, no systematic work so far has detailed the factors affecting the polydispersity of chitosan as an important factor determining the quality of many preparations. Herein, using artificial neural networks (ANNs), four independent variables, namely, pH and concentration of chitosan solution as well as time and amplitude of sonication of the solution were studied to determine their influence on the polydispersity of solution. We found that in an ultrasound prepared nanodispersion of chitosan, all the four input parameters have reverse but non-linear relation with the polydispersity of the nanoparticles.